Rationalization of hydrogen production by bulk g-C3N4: an in-depth correlation between physico-chemical parameters and solar light photocatalysis. Issue 69 (26th November 2018) - Speltini, Andrea; Pisanu, Ambra; Profumo, Antonella; Milanese, Chiara; Sangaletti, Luigi; Drera, Giovanni; Patrini, Maddalena; Pentimalli, Marzia; Malavasi, Lorenzo
Abstract : Extensive physico-chemical investigation on bulk g-C3 N4 allowed a reliable correlation between hydrogen production and materials properties to be established. Abstract : The aim of this work is the systematic study of the photocatalytic activity of bulk graphitic carbon nitride (g-C3 N4 ) in relation with the physical–chemical, structural and optical properties of the semiconductor. Fourteen g-C3 N4 samples have been prepared by thermal condensation starting from three different precursor (melamine, dicyandiamide and urea) and exploring various temperatures (in the range 500–700 °C). The materials obtained have been deeply characterized by high resolution scanning electron microscopy, thermogravimetric analysis, X-ray diffraction, nitrogen adsorption measurements (BET method), X-ray photoelectron spectroscopy and diffuse reflectance spectroscopy. Each semiconductor, coupled with Pt co-catalyst, was tested for hydrogen gas production from aqueous triethanolamine as model sacrificial agent, under simulated solar light. The hydrogen evolution profiles turned out to be strictly dependent on precursor type and synthesis temperature, with the highest evolution rate observed for the samples series produced from urea (up to ca. 4400 μmol g −1 h −1 ). The results, corroborated by the excellent inter-day precision of irradiation tests (RSD < 5%, n = 3) together with the good batch-to-batch reproducibility (RSD < 11%, n = 3), were critically discussed. Apart from the appealing production values obtained using the as-prepared materials, it was importantly pointed out that, besides crystallinity and visible light absorption, the photocatalytic behavior is definitely correlated to the surface area, which is dependent on the synthesis conditions, that is polymerization temperature and nature of g-C3 N4 precursor. Overall, this systematic investigation demonstrated that, contrary to the polymerization degree (sp 2 /sp 3 carbon ratio), surface area is the real determinant parameter for g-C3 N4 hydrogen evolution activity.